2022
DOI: 10.3390/coatings12010049
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Interactions with Covalently Grafted 2D Nanometric Carboxyphenyl Thin Films—An Experimental and DFT Study

Abstract: Surface modification is a hot topic in electrochemistry and material sciences because it affects the way materials are used. In this paper, a method for covalently attaching carboxyphenyl (PhCOOH) groups to a gold electrode is presented. These groups were grafted onto the electrode surface electrochemically via reduction of aryldiazonium salt. The resulting grafted surface was characterized using cyclic voltammetry (CV) before and after the functionalization procedure to validate the presence of the grafted la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…2 were more than 60 kcal/mol. These numbers are suggestive of the establishment of an interface that is stable 43 . The layers generated by grafting radicals are more stable than previously documented surface modification processes based on the formation of self-assembling monolayers (SAM) through thiol chemistry (BDE|Au-S-(CH 2 ) 5 -COOH|= 31.59 kcal/mol).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…2 were more than 60 kcal/mol. These numbers are suggestive of the establishment of an interface that is stable 43 . The layers generated by grafting radicals are more stable than previously documented surface modification processes based on the formation of self-assembling monolayers (SAM) through thiol chemistry (BDE|Au-S-(CH 2 ) 5 -COOH|= 31.59 kcal/mol).…”
Section: Resultsmentioning
confidence: 96%
“…We investigated the reactions that the aryl radicals (phenyl and nitrophenyl) and the alkyl radical (hexyl) had with the B 12 N 12 nanocage cluster. It has been previously confirmed that the Bond Dissociation Energy (BDE) is a significant parameter that can be used to evaluate the strength of the interface while the grafting process is taking place 25,26,41,[43][44][45][46] .…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the computation of the Bond Dissociation Energy, or BDE, is useful for determining how stable is the newly created interface. [ 35 , 36 ] To compute the BDE, a simple model of the surface lignite (presented in Figure 11 ) is grafted covalently by a phenyl group. The model of Kosovo lignite is the same as it was used previously.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure B, the presence of carboxyphenyl groups of diazonium salt can be confirmed by peaks observed at 1520 and 1660 cm –1 (blue). These peaks may be attributed to the aromatic and/or carboxylic acid groups, and they vanish after the attachment of PPG (red) . The C–O stretching peaks of PPG appear in the 1000–1500 cm –1 range, and the 2865 and 2972 cm –1 peaks indicate the presence of C–H groups of PPG …”
Section: Resultsmentioning
confidence: 99%
“…These peaks may be attributed to the aromatic and/or carboxylic acid groups, and they vanish after the attachment of PPG (red). 37 The C−O stretching peaks of PPG appear in the 1000−1500 cm −1 range, and the 2865 and 2972 cm −1 peaks indicate the presence of C−H groups of PPG. 36 XPS analysis was performed to verify the EIS and ATR-FTIR results (Figure 3C and Figure 3D).…”
Section: Resultsmentioning
confidence: 99%